Removal of Selenium (Se) and Zinc (Zn) inWater by Using Natural Zeolitic Tuff as Adsorbent from Tegalrejo Area, Gedangsari District, Gunungkidul Regency, Special Province Yogyakarta, Indonesia - Manixone Thepgnothy; Doni Prakasa Eka Putra; Wahyu Wilopo (Journal of Applied Geology, 2018)
Heavy metals are one of the most hazardous pollutant in the water. Thereare many methods for heavy metals remediation such as precipitation, oxidation, reverseosmosis, ion exchange and sorption by reactive materials. Zeolite is one of reactive materials have been used for water remediation. Therefero, in this the capability of zeolite from Gedangsari District, Gunung Kidul Regency, Special Province of Yogyakarta, Indonesia, will be invetigated to remidiate contaminated water by selenium (Se) and Zinc (Zn). To answer this objective, several samples of natural zeolitic tuff were taken and charaterized. Laboratory experiment was done by batch test. The results showed that natural zeolitic tuff is an effective adsorbent of Se and Zn and holds great potential material to remove heavy metals in water. The sorption isotherms of Se and Zn confirmed to type of Langmuir or Freundlich isotherms.